Mitral Multifocal Papillary Fibroelastoma in a Patient with Aggressive Fibromatosis - Müller, Philipp P.; Agaimy, Abbas; Weyand, Michael; Heim, Christian (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Mitral valve fibroelastoma is a rare condition that can be associated with high morbidity rates due to thrombus formation and resulting embolic events. Causative treatment for affected patients is mitral valve surgery. An association between cardiac fibroelastoma and desmoid-type fibromatosis, an aggressive form of fibromatosis, is not yet described. We present a case of a 58-year-old man with a history of desmoid-type fibromatosis and concomitant papillary fibroelastoma of the mitral valve who consequently underwent mitral valve replacement.
Keywords: histology; mitral valve surgery; tumor; cardiac